Study Of Gender Exploitation In Munshi Premchand Stories - Gupta, Surendra Kumar (International Journal of Psychosocial Rehabilitation, 2011)
Indian society has been divided on basis of Varna system which was the core of the sociallife of the society in the past. One could not think of going beyond that or violate the set norms for them. The condition of woman in particular was very pathetic and weak in this classified society. The present paper is going to discuss the oppression of the weak and poor at the hand of rich and powerful through Premchand’s stories Vidhwans (Catastrophe) and Garib Ki Hai(Power of Curse). Vidhwans is the story of an old childless widow named Bhungi who has to sacrifice her life in fire because of the exploitation of the village owner, Pandit Udaibhan Pandeyand Garib Ki Hai presents the exploitation of Munga, a Brahman widow by Mushi Ramshevak. He did not return her money which leads to the miserable and untimely death of Munga. After her death, the destruction of the family of Ramsavak begins. These stories narrated the conditions of rural India where these varna system is religiously followed.